Feasibility study of adaptive radiotherapy with Ethos for breast cancer - Galand, Arthur; Prunaretty, Jessica; Mir, Nicolas; Morel, Aurélie; Bourgier, Céline; Aillères, Norbert; Azria, David; Fenoglietto, Pascal (Frontiers in Oncology, 2023)
The aim of this study was to assess the feasibility of online adaptive radiation therapy with Ethos for breast cancer. This retrospective study included 20 breast cancer patients previously treated with TrueBeam. All had undergone breast surgery for different indications and were evenly divided between these four cases, with 5 extended CBCTs per patient. The dataset was used in an Ethos emulator to test the full adaptive workflow. The contours generated by artificial intelligence (AI) for the influencers (left and right breasts and lungs, heart), and by elastic or rigid deformation for the target volumes (internal mammary chain (IMC) and clavicular lymph nodes (CLN)) were compared to the initial contours delineated by the physician using two metrics: Dice similarity coefficient (DICE) and Hausdorff 95% distance (HD95). The times taken by the emulator to generate contours, optimize plans and calculate doses were recorded. The quality of the scheduled and adapted plans generated by Ethos was assessed using PTV coverage, homogeneity indices (HI) and doses to organs at risk (OAR) via DVH metrics. Quality assurance (QA) of treatment plans was performed using an independent portal dosimetry tool (EpiQA) and gamma index. On average, the DICE for the influencers was greater than 0.9. Contours resulting from rigid deformation had a higher DICE and a lower HD95 than those resulting from elastic deformation, but remained below the values obtained for the influencers: DICE were 0.79 ± 0.11 and 0.46 ± 0.17 for CLN and IMC, respectively. The mean time for contour generation per AI was 73 ± 4 s and 80 ± 9 s for deformations. The average time for dose calculation was 53 ± 3s and for plan optimisation 125 ± 9s. A dosimetric comparison of scheduled and adapted plans showed a significant difference in PTV coverage: D95% were higher and closer to the prescribed doses for adapted plans. Doses to organs at risk were similar. The average gamma index for quality assurance of adapted plans was 99.93 ± 0.38 for a 3%/3mm criterion. This study comprehensively evaluated the Ethos® adaptive workflow for breast cancer and its potential technical limitations